(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cutibacterium acnes (C. acnes) plays a key role in the pathogenesis of acne. Studies on antibiotic resistance of this microorganism are being conducted in many countries, but systematic reviews and meta-analyses on this topic are still lacking. The aim of this study was to systematically assess the level of resistance of C. acnes to various antibiotics in order to form rational approaches to antibiotic therapy of acne.